2016
DOI: 10.1007/s12031-016-0854-0
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Transporter 3 (Znt3) as an Active Substance in the Enteric Nervous System of the Porcine Esophagus

Abstract: Zinc transporter 3 (ZnT3), a member of the SLC 30 zinc transporter family, is involved in the transport of zinc ions from the cytoplasm into synaptic vesicles or intracellular organelles. The aim of the present study was to investigate for the first time the percentage of ZnT3-like immunoreactive (ZnT3-LI) neurons in the enteric nervous system (ENS) of the porcine esophagus and denotation of their neurochemical coding. Routine double- and triple-immunofluorescence labeling of cervical, thoracic, and abdominal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…After at least 2 weeks, the fragments of liver were frozen at -23°C and cut into 10 μm-thick sections using a microtome (Microm, HM 525, Walldorf, Germany). The sections were subjected to a routine single-labelling immunofluorescence technique according to the method described previously by Gonkowski and Wojtkiewicz [17,18,35,59]. A condensed description of the method is as follows: 45 min of drying; incubation with a blocking solution, which included 10% normal goat serum, 0.1% bovine serum albumin, 0.01% NaN3, Triton ×-100 and thimerozal in phosphate buffered saline (PBS) for 1 h; overnight incubation with a polyclonal "primary" antibody directed towards SP, GAL, PACAP, CGRP, or CART; incubation (for 1 h) with species-specific antisera conjugated to fluorescein isothiocyanate (FITC) or biotin, which was visualised by a streptavidin-CY3 complex (the specification of primary and secondary antibodies used in the present study is shown in Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…After at least 2 weeks, the fragments of liver were frozen at -23°C and cut into 10 μm-thick sections using a microtome (Microm, HM 525, Walldorf, Germany). The sections were subjected to a routine single-labelling immunofluorescence technique according to the method described previously by Gonkowski and Wojtkiewicz [17,18,35,59]. A condensed description of the method is as follows: 45 min of drying; incubation with a blocking solution, which included 10% normal goat serum, 0.1% bovine serum albumin, 0.01% NaN3, Triton ×-100 and thimerozal in phosphate buffered saline (PBS) for 1 h; overnight incubation with a polyclonal "primary" antibody directed towards SP, GAL, PACAP, CGRP, or CART; incubation (for 1 h) with species-specific antisera conjugated to fluorescein isothiocyanate (FITC) or biotin, which was visualised by a streptavidin-CY3 complex (the specification of primary and secondary antibodies used in the present study is shown in Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, Zrt-like, Irt-like protein (ZIP)4 is highly important since it is expressed along the entire GI tract acting as a major processor of zinc uptake into enterocytes from the apical membrane [ 26 ]. Moreover, zinc transporter (ZnT)3, is highly expressed in the human large and porcine small intestine and the esophagus [ 27 , 28 ]. Herein, its concrete function in the GI tract is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is known that besides extrinsic cholinergic innervation, the oesophageal motor endplates also receive information from enteric neurons located in ganglionated plexuses positioned in the wall of the oesophagus (Wu et al., ). This information in pigs is transmitted with neuronal factors typical of the enteric nervous system (Wojtkiewicz et al., ). The wide range of such substances that may be involved in the innervation of the oesophageal motor endplates was confirmed by this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The neurochemical characterization of neuronal structures located in the stomach and intestine is relatively well known both under physiological conditions and during various pathological processes (Brown & Gulbransen, ; Ferri et al., ; Gonkowski et al., ). Contrary to the abovementioned fragments of the GI tract, the knowledge of the chemical coding of the neuronal structures in the oesophagus, especially in pigs, is rather scanty (Wojtkiewicz, Makowska, Bejer‐Olenska, & Gonkowski, ; Wu et al., ). For this reason, the aim of this study was to investigate the neurochemical characterization of nerve fibres located in the muscular and mucosal layers of various parts of the porcine oesophagus.…”
Section: Introductionmentioning
confidence: 99%